A contribution to the systematics of Australasian Tanytarsini (Diptera: Chironomidae): first descriptions from New Caledonia - Giłka, Wojciech; Dobosz, Roland (Zootaxa, 2015)
First specific records of chironomids of the tribe Tanytarsini from New Caledonia based on detailed descriptions of new species are presented. Cladotanytarsus (Cladotanytarsus) stylifer sp. nov. and its closest relatives, i.a. Cladotanytarsus (C.) isigacedeus (Sasa et Suzuki, 2000), comb. nov., known from males bearing extraordinarily elongate hypopygial anal points are diagnosed. Paratanytarsus mirificus sp. nov. is described as adult male with unique structure of its hypopygium and shortened antennae. Diagnostic description of Tanytarsus fuscithorax Skuse, 1889 is also complemented.